A case of hypogonadotrophic hypogonadism with anosmia (Kallmann's syndrome) in a male, with familial incidence of a small metacentric chromosome (47, XX, mat?+). Issue 1 (February 1976) - Ventruto, V; Cali, A; Farina, L; Festa, B; Ricciardi, I; Sebastio, L
Abstract : A case of Kallmann's syndrome in a male is reported. Besides the classical picture of hypogonadotrophic hypogonadism (demonstrated both by endocrine investigation and a testicular biopsy) with anosmia, a number of other unusual features are present including gynaecomastia, agencies of the anterior brachial muscles, some dental abnormalities, and dyschromatopsy. The karyotype, studied on peripheral lymphocytes, shows, in the propositus as well as in his mother, the presence in all mitoses of an extra small metacentric chromosome; its derivation is uncertain.